Bergman e o sonho : a narrativa cinematográfica como processo de construção onírica - Menegat, Marceli (2023)
This research aims to study the dream narrative from the Freudian psychoanalytic theory and the cinematographic narrative from three films by the Swedish director Ingmar Bergman, namely The Seventh Seal (1957), Persona (1966), and Hour of the Wolf (1968) in order to investigate the possible relations between dream construction and narrative construction in cinema. In this sense, the investigation seeks to understand how the construction of the cinematographic narrative takes place from the specific aspects of this artistic way of doing and therefore to find the possible connections and proximities with the dream narrative from its construction thought by Sigmund Freud in his work The Interpretation of the Dream (1900). Three common elements were found between the two narratives: figurability, external elements and daytime remains and the regression process. For the analysis of these aspects, scenes from the chosen films were used, relating them to the Freudian theory presented in the text. Other data were studied, such as the importance of displacement and condensation and the preparation of the environment for, on the one hand, the process of dreaming, which implies sleep and the act of sleeping, and, on the other hand, the aesthetic fruition of the film that presupposes the suspension of consciousness that allows the spectator's catharsis in relation to the narrative.